Sonic the hedgehog 3 [videorecording (DVD)] - Carrey, Jim, 1962-; Marsden, James, 1973- (Paramount, 2025)
Sonic the Hedgehog returns to the big screen this holiday season in his most thrilling adventure yet. Sonic, Knuckles, and Tails reunite against a powerful new adversary, Shadow, a mysterious villain with powers unlike anything they have faced before. With their abilities outmatched in every way, Team Sonic must seek out an unlikely alliance in hopes of stopping Shadow and protecting the planet.